History of dental caries and need for dental treatment of children with visual disabilities, Chile, 2014. - Marco Guidotti; Katalina Hernández; Giorgio Salvatori; Carolina Vergara (Universidad de Concepción., 2014)
Objective: To determine the history of dental caries and the need for dental treatment of children with visual disabilities 6-12 years, belonging to Chile Special Schools, 2014.Material and Methods: A descriptive cross-sectional observational study. The target population was children with visual disabilities in special schools in Chile. A clinical examination was performed to obtain a deft, DMFT and the need for treatment. Two calibrated examiners performed the visual clinical examination, according to the WHO criteria. Additionally, lesions clinically detectable enamel surfaces cavitated and not cavitated recorded. The recorded data were analyzed using descriptive statistics.Results: Ninety-four children were examined, belonging to 7 special schools. The average dmft was 2.05 (SD±2.6) and DMFT was 0.96 (SD±1.3). At 6 years, the dmft/ DMFT was 3/0 respectively. At 12 years dmft was 0.17 and DMFT was 1.42. Caries prevalence was 56.3%. 95% of children need sealants, 50% need at least a restoration of a face, and 29% restoration of 2 or more surfaces. As for enamel lesions, 34% of children had at least one lesion not cavitated and 48% of them had a cavitated lesion. Conclusion: The history of dental caries is similar to that reported in the general population; however, there is a high need for preventive treatment, so it is necessary to conduct more research to clarify whether these patients have a higher cariogenic risk due to alteration visual, so as to establish promotional / preventive effective strategies.